Conjunto de bases Gaussianas aumentado de qualidade quádrupla zeta de valência para os átomos K e Sc-Kr : aplicação em cálculos HF, MP2 e DFT de propriedades elétricas moleculares - Martins, Lucas Sousa Carvalho (2013)
Augmented Gaussian basis set of quadruple zeta valence quality plus polarization functions for the atoms K and from Sc to Kr is presented. It was constructed from the allelectron unaugmented set by addition of diffuse functions (s, p, d, f, g, and h symmetries) that were optimized for the anion ground states. From this set, Hartree-Fock, secondorder Møller-Plesset perturbation theory, and density functional theory electric dipole moment and polarizabilities for a sample of molecules as well as for Cun (n 6 4) clusters were calculated and compared with theoretical and experimental values available in the literature